Teacher Leadership in Hybrid Learning - Juharni, Indra; Hidayati, Dian; Usmar, Rahmannisa Juita (Universitas Pendidikan Indonesia, 2021)
Hybrid learning is learning that combines face-to-face learning methods with online learning. Hybrid learning is a solution when face-to-face learning is limited. The role of teacher leadership in Hybrid learning is important because teachers must be able to lead discussions between students in class and online in a coherent manner. Through this research, teacher leadership in Hybrid learning will be revealed as information, evaluation, or improvement material for school principals. The method in this research is descriptive qualitative. Data collection techniques using a questionnaire. Data analysis uses descriptive statistics by calculating the percentage, then categorizes it into three categories, namely high, medium, and low. The results of the study were 15.38% high leadership, 65.38% moderate leadership, and 19.23% low. In the aspect of organizing learning 15.38% high, 69.23% moderate, and 15.38% low. In the aspect of learning evaluation 23.08% high, 53.38% moderate, and 23.08% low.